The Interactive Learning Strategy in The Reading Lesson among University Students in The Fourth level "A" Intensive Programs at Al-Amien Islamic University Prenduan Sumenep Madura for The Academic Year 2022-2023 - Uswatun Hasanah; Kamilatus Sholehah (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
The learning method is very important in preparing the learning process activities.The teacher have to consider choosing strategies and models that are relevant to the learning methods that will be used during the learning process. Specially in learning mutholaah semester IV A IDIA Prenduan. This subject difficult to understand because the story of the text is in Arabic Language. The interactive learning strategy is an effective and efficient strategy for creating an active and interactive class to help the students to understand. The purpose of this study was to find out the steps of interactive learning strategy in mutholaah learning for Semester IV A IDIA Prenduan, and the supporting factors and inhibiting factors in interactive learning strategies of this subject. This study used a qualitative descriptive approach. The methods of collecting data use interviews, observation and documentation. The results of the interactive learning strategy in mutholaah learning for students in semester IV A IDIA Prenduan is, in the mutholaah learning process the teacher uses many steps, are preparation stage, the initial knowledge stage, the activity stage, the student question stage, the investigation stage, the final knowledge stage, the reflection stage and application. The several supporting factors in this learning are thinking skills, student enthusiasm, and student cooperation, while the inhibiting factors are lack of vocabulary mastery, Minimal language acquisition, and discussion preparation.